2021
DOI: 10.1016/j.ajoc.2021.101139
|View full text |Cite
|
Sign up to set email alerts
|

A case of infectious crystalline keratopathy after corneal cross-linking

Abstract: Purpose To present a case of infectious crystalline keratopathy after corneal cross-linking in a child with delayed wound healing, and its successful management with antibiotic and anti-fungal eye drops. Observations A 14-year-old male presented for a second opinion with a non-staining crystalline keratopathy after corneal crosslinking for progressive keratoconus. He reportedly rubbed his eyes vigorously in the post-operative course and had a slowly healing epithelial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The authors concluded that systemic immunosuppression did not result in serious adverse effects and was relatively safe [ 241 ]. However, immunosuppression can cause persistent epithelial defects and increase the risk for infectious keratitis, especially fungal keratitis [ 243 ].…”
Section: Therapy Of Lscdmentioning
confidence: 99%
“…The authors concluded that systemic immunosuppression did not result in serious adverse effects and was relatively safe [ 241 ]. However, immunosuppression can cause persistent epithelial defects and increase the risk for infectious keratitis, especially fungal keratitis [ 243 ].…”
Section: Therapy Of Lscdmentioning
confidence: 99%